Exploring the influence of social media communication and brand image on international student enrollment intentions in higher education - Li, Shuwu; Quan, Yuzhen; Xiao, Liqing; Ren, Haixia; Abinova, Alfiya Yuriyevna (Frontiers in Education, 2025)
This study examines how social media communication and brand image influence international students’ enrollment intentions in higher education institutions, particularly in response to China’s declining birth rate and increasing number of college graduates. Official data projects an “overcapacity” of over 2.79 million in mainland China’s universities by 2024, with an excess rate of 23.6%. Strategies such as enhancing institutional standards and expanding international student enrollment are being considered to address these trends. Using data from 156 foreign students at three upgraded colleges in Guangxi, this paper explores the roles of user-generated and school-generated contents in social media communication, as well as brand image development factors. Partial least squares regression was employed to evaluate the measurement model and hypotheses. The analysis reveals that social media communication and brand image positively affect brand preference, with brand image mediating their relationship. Interactivity, transparency, and authenticity on social media platforms, along with academic reputation, internationalization, and cultural diversity, significantly influence enrollment intentions. This research offers practical guidance for universities aiming to enhance their brand image via social media to attract more international students, addressing demographic and institutional challenges.